Between dogma and doubt: A meta‐synthesis of innovation in the public sector. Issue 1 (5th July 2021) - Al‐Noaimi, Hessa A.; Durugbo, Christopher M.; Al‐Jayyousi, Odeh R.
Abstract: Public sector innovation is a management paradigm that introduces novel actions and artefacts in confronting societal challenges. However, the enabling or inhibiting role of innovation remains a conundrum that necessitates on‐going analysis and critique for advancing public management discourse and scholarship. The purpose of this article is to analyse the drivers and barriers to innovation in the public sector based on a meta‐synthesis of management literature. In‐depth analysis of 21 qualitative studies reporting on innovation in the public sector identifies five themes for drivers and barriers. Insights from the synthesis pose research challenges for public sector organisations to look beyond praxis to crisis, discover co‐creative radius, recognise ambiguous capacities, and attain integrative intelligence. Using insights from identified concepts and themes, the article develops a line of argument on the contextualisation of innovation for public management and sheds light on areas for future research on public sector innovation. Abstract : This article makes contributions on several conceptual areas, namely: assemblage of sources provides a comparative analysis of qualitative studies on public sector innovation that covers the opinions and experiences of participants around the world, giving insights on the diversity of mindsets and mores. Second, the meta‐synthesis of sources presents a diagnostic refutation of the literature by tracing specific patterns that build a ground of justifications that contribute to resolving the conundrum of innovation between drivers and barriers. These justifications eliminate some of the ambiguity surrounding innovation processes in this sector and suggest a logical notion of the need to appraise innovation without separating it from its structural and behavioral contexts. Lastly, the hypothetical model contributes to directing the collective awareness and research efforts towards unconventional dimensions by presenting objective perceptions for DUI strategies that give public sector innovation its full capacity.